AB0967 Is the icoap a valid tool for measuring pain and function in patients with knee oa and ra in clinical practice?. (12th June 2018) - Obire, J.; Harrison, A.; Sofat, N.
Abstract : Background: Osteoarthritis (OA) is primarily managed in general practice however, care is provided on an ad hoc basis, and a structured approach to continuing care is not offered. Studies have demonstrated the high prevalence of secondary OA of the knee in patients with RA, however, about 52% of these cases are underreported or under graded by general radiological reports. With its increasing prevalence, it is important to use valid and responsive instruments to evaluate the effectiveness of interventions and to understand the pathology's impact on functioning and general health status. Objectives: We hypothesised that the ICOAP can accurately measure the severity of pain in patients with OA in the clinical setting and can equally detect secondary OA in patients with pre-existing RA. Methods: Patients with longstanding knee OA or RA from outpatient rheumatology clinics alongside GP surgeries were recruited. The ICOAP's formatting was modified and brief abstract was added to the top of the questionnaire to aid patient comprehension. After its modification, it was tested for internal consistency, reliability and construct validity by correlating its yield with other disease activity parameters including the WOMAC and DAS. To examine the test-retest reliability patients were asked to fill out the ICOAP questionnaire again after two weeks. Results: The study included 57 patients with OA and 45 with RA. Total ICOAP-C was 42 with patients with OA compared to 56 in patients with RA while ICOAP-I was 49 in patients with OA compared with 53 in patients with RA. Subgroup analysis of ICOAP-C and ICOAP-C identified that while intermittent pain had a greater impact on QOL in patients with OA, constant pain had a greater impact on OA patient QOL. Patients with RA for more than 10 years had more similar results to patients with OA. Conclusions: The ICOAP questionnaire is easy to use clinically, with the majority of patients approached willing to participate. Respondents with both OA and RA also commented on the lack of complication and ease of understanding of questions. It was responsive to changes in management, proving to be a useful tool in general practice to follow disease progression. The findings demonstrate that the ICOAP has a potentially wider clinical utility in measuring pain in patients with both OA and RA. The similarities in responses of the majority of respondents with knee OA and long-standing RA also strongly suggest that ICOAP might be likely detecting under-reported secondary OA. Future research will examine the effects of variables like pain catastrophizing on pain perception and response. References: [1] Hawker, G. et al, (2008). Development and preliminary psychometric testing of a new OA pain measure – an OARSI/OMERACT initiative. Osteoarthritis and Cartilage, 16(4), pp.409–414. [2] Pincus, T. et al, (2016). Secondary osteoarthritis appears as severe as inflammation in contemporary care of rheumatoid arthritis: Implications for therapeutic approaches. Osteoarthritis and Cartilage, 24, pp.S235-S236. [3] Ferrier, J. et al, (2005). P226 Representation of the severity of osteoarthritis of the knee by standard radiographs. Osteoarthritis and Cartilage, 13, p.S113. Disclosure of Interest: None declared